A tax proposal for a cash flow corporate tax - Lourdes Jerez Barroso; Joaquín Texeira Quirós (Intangible Capital, 2013)
Purpose: Due to its advantages in terms of neutrality and simplicity, the aim of this paper is to design a tax base for corporation cash flows, as well as to develop its practical implementation. Design/Methodology: The conceptual aspects and the background of tax on corporation tax flows are reviewed and a tax base that levies a charge on the corporation’s economical activities’ cash flow is then proposed. In order to carry this out, a methodological procedure is developed on the basis of the accounting documents that companies must present and through which the stock variables and the accounting documents’ work flow is transformed into cash flow. Findings: An implementation on the basis of the accounting documents that Spanish companies must present. Practical Implications: This paper defines the procedure to follow in order to determine the tax base of a cash flow corporate income tax on the basis of its accounts, which would allow an estimation of this tax figure’s revenue impact. Originality/ Value: The design of a tax base of cash flows for companies. The accounting approximation carried out to determine the cash flows justifies the fact that the tax base proposal is technically possible.